2022
DOI: 10.3390/su14052843
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Collaboration on Enterprises Internationalization Process

Abstract: At present, competitive globalized environments force enterprises to make more effort to both set up collaborative processes among networked partners and open their borders to the internationalization process. With this participation in internationalization processes, a set of barriers emerges that enterprises must overcome, particularly SMEs. The internationalization barriers are classified in four main dimensions, namely, strategy, technology, partners and product, which are considered to establish relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Uppsala's internationalisation model made mentions of effectuation without going into detail about the decisions made by firms during internationalisation (Dow et al 2018;Andres et al 2022), but performance is also affected by internationalisation speed (Mohr and Batsakis 2017;Vanninen et al 2022), which can be understood as the change rate of the internationalisation process, once the firm has already entered the international market (Zahoor and Al-Tabbaa 2021). Trust fosters internationalisation because it reduces uncertainty (Anderson and Jap 2005;Foli et al 2022), especially in foreign markets and when dealing with foreign firms (Johanson and Vahlne 2009;Andres et al 2022). For this needed resource commitment and allocation, a choice should be made between planned decisions (causal decisions) and those that leverage available resources and opportunities over planning (effectual decisions) (Sarasvathy 2001).…”
Section: Effectuation Vs Causation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Uppsala's internationalisation model made mentions of effectuation without going into detail about the decisions made by firms during internationalisation (Dow et al 2018;Andres et al 2022), but performance is also affected by internationalisation speed (Mohr and Batsakis 2017;Vanninen et al 2022), which can be understood as the change rate of the internationalisation process, once the firm has already entered the international market (Zahoor and Al-Tabbaa 2021). Trust fosters internationalisation because it reduces uncertainty (Anderson and Jap 2005;Foli et al 2022), especially in foreign markets and when dealing with foreign firms (Johanson and Vahlne 2009;Andres et al 2022). For this needed resource commitment and allocation, a choice should be made between planned decisions (causal decisions) and those that leverage available resources and opportunities over planning (effectual decisions) (Sarasvathy 2001).…”
Section: Effectuation Vs Causation Theorymentioning
confidence: 99%
“…This research provides a significant contribution, something new and powerful about IE and MCS in small, young firms. Factors such as organisational structure, experience, and training determine a firm's success in the internationalised context (Freixanet et al 2020;Andres et al 2022;Foli et al 2022;Uzhegova and Torkkeli 2022;Vanninen et al 2022). However, the age of the organisation and the degree of professionalism of the management as they impact on management style and the use of control mechanisms are scarcely analysed yet, which could improve the relationships in MCS to achieve local and global control needs.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the efficacy of numerous efforts, such as financial aid programs, tax breaks, and regulatory changes [55,56]. They have also considered the significance of establishing networks and collaborations among SMEs, universities, and other stakeholders in order to foster innovation and knowledge-sharing [57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that collaborative intensity enhances SMEs’ ability to benefit from internationalization and increase their international growth (Cesinger et al, 2016; Swoboda et al, 2011). Andres et al (2022) showed that the internationalization process of Spanish SMEs is facilitated by collaboration with international partners. Similarly, Zahoor et al (2020) underlined that the SMEs’ pace of entering foreign market, international growth, and international diversification depend mainly on their collaboration capabilities.…”
Section: Introductionmentioning
confidence: 99%